Pediatric Lichen Myxedematosus: A Diagnostic and Management Challenge - Kelly K. Barry; Diana B. Reusch; Birgitta A. R. Schmidt; Elena B. Hawryluk (MDPI AG, 2022)
Localized lichen myxedematosus (LM) is a rare, idiopathic mucinosis characterized by dermal mucin deposition and variable fibroblast proliferation. Nodular lichen myxedematosus, a clinicopathologic subtype of localized LM, is exceedingly rare in pediatric patients with only three prior cases reported. Understanding of LM in pediatric patients is limited by the rarity of the disease, and diagnosis is complicated by overlapping clinical and histopathologic features. There is no standardized treatment for localized LM and treatment is largely dictated by a patient's desire to minimize cosmetic disfigurement. This case series reports two additional patients with juvenile nodular lichen myxedematosus, highlights the limitations of existing diagnostic criteria, and describes successful treatment of one patient with intralesional triamcinolone.